CIVIC EDUCATION BARCODE MEDIA REVIEWED FROM 21ST CENTURY SKILLS LEARNING - Supriadi; Rahmad Rafid; Shellya Tanaya Dhayinta; Riski Febria Nurita (Four Son Scholarship, 2024)
In this article, we will discuss the use of Civic Education barcode media in terms of 21st century skills learning. The use of Civic Education barcode media will be reviewed to see whether it can support the implementation of 21st century skills learning. Whether 21st century skills are already present in the use of Civic Education barcode media will be discussed, so it is hoped that their utilization can be achieved. can run optimally in the future if you have found the emphasis on 21st century skills. This writing was carried out using literature study. All skills contained in Skill 21 learning can be possessed by students if teachers are able to create learning that supports the implementation of 21st century skills. Teachers develop learning that contains activities that challenge students to think critically and solve problems. Learning activities must also encourage students to work together and communicate so that learning skills 21 are visible. In this article, we will discuss the use of Civic Education barcode media in terms of 21st century skills learning. The use of Civic Education barcode media will be reviewed to see whether it can support the implementation of 21st century skills learning. So it is hoped that its use can run optimally in the future if we have found the emphasis on 21st century skills